Crystal Structure and Optical Properties of Al-Doped ZnO Large-Area Thin Films Using 1500 mm Dual Cylindrical Cathodes - Lee, JinJu; Ha, Jong-Yoon; Yim, Haena; Choi, Won-Kook; Cho, Ji-Won (AMER SCIENTIFIC PUBLISHERS, 2015)
The large-area Al-doped ZnO thin films are successfully deposited at room temperature on polycarbonate substrate using a 1500 mm dual cylindrical cathodes sputtering system. Those thin films have smooth surfaces (RMS: 9.6 nm) and lower thicknesses deviation (Uniformity: 98.6%) despite of high RF power. The optical transmittance properties of 3.13 wt% Al doped ZnO thin films have above 85% in visible region. A dual cylindrical cathodes sputtering system can fabricate transparent electrode on flexible electronic devices at room temperature for mass production of 6th generation solar cell and display industry.
Keywords: TRANSPARENT CONDUCTING ZNO; ELECTRICAL-PROPERTIES; LAYER; OXIDE; TEMPERATURE; GROWTH